Cholecystokinin octapeptide stimulates phasic and tonic pyloric motility in healthy humans. Issue 1 (January 1993) - Fraser, R; Fone, D; Horowitz, M; Dent, J
Abstract : Stimulation of localised pyloric contractions may be an important mechanism in the slowing of gastric emptying by cholecystokinin infusion. The effect of cholecystokinin octapeptide on fasting pyloric motility was investigated in 14 healthy volunteers. Antral, pyloric, and duodenal pressure responses to normal saline and graded injections of cholecystokinin octapeptide (5, 10, and 20 ng/kg) were measured. Injections were given double blind and in randomised order. All doses of cholecystokinin octapeptide initially stimulated (p < 0.05 cf saline) phasic pressure waves localised to the pylorus--the median number of pyloric pressure waves in the 5 minutes after injection being 0, 3.5, 6, and 7 for the saline and the 5, 10, 20 ng/kg cholecystokinin octapeptide injections respectively. The phasic pyloric motor response to 20 ng/kg cholecystokinin octapeptide injection was greater than that to 5 ng/kg (p < 0.05). Basal pyloric pressure increased after 20 ng/kg (1.0 v 0.2 mm Hg, p < 0.05 cf saline). Antral and duodenal pressure waves were suppressed initially by all doses of cholecystokinin (p < 0.05 cf saline). Subsequently, 20 of the 42 cholecystokinin octapeptide, injections but none of the saline injections, were followed by antropyloric pressure waves. Atropine, 15 micrograms/kg iv as a bolus, and then 4 micrograms/kg/hour iv as an infusion, had no effect on the stimulation of localised phasic pyloric pressure waves by cholecystokinin octapeptide 10 ng/kg. It is concluded that stimulation of pyloric contractions and suppression of antral and proximal duodenal motility may contribute to the slowing of gastric emptying produced by cholecystokinin.